Integrated real-time imaging system, 'IRIS', Kangaroo feeding tube: a guide to placement and image interpretation. Issue 1 (28th October 2021) - Taylor, Stephen; Sayer, Kaylee; Milne, Danielle; Brown, Jules; Zeino, Zeino
Abstract : Background: Lung complications occur in 0.5% of the millions of blind tube placements. This represents a major health burden. Use of a Kangaroo feeding tubes with an 'integrated real-time imaging system' ('IRIS' tube) may pre-empt such complications. We aimed to produce a preliminary operator guide to IRIS tube placement and interpretation of position. Methods: In a single centre, IRIS tubes were prospectively placed in intensive care unit patients. Characteristics of tube placement and visualised anatomy were recorded in each organ to produce a guide. Results: Of 45 patients having one tube placement, 3 were aborted due to refusal (n=1) or inability to enter the oesophagus (n=2). Of 43 tubes placed beyond 30 cm, 12 (28%) initially entered the respiratory tract but all were withdrawn before reaching the main carina. We identified anatomical markers for the nasal or oral cavity (97.8%), respiratory tract (100%), oesophagus (97.6%), stomach (100%) and intestine (100%). Organ differentiation was possible in 100%: trachea-oesophagus, oesophagus-stomach and stomach-intestine. Gastric tube position was confirmed by aspiration of fluid with a pH < 4.0 and/ or X-ray. Trauma was avoided in 13.6% by identifying that the tube remained in the nasal lumen in the presence of a base of skull fracture (n=3) and in the stomach in the presence of recently bleeding polyps or mucosa (n=3). A systematic guide was produced from records of tube placement and interpretation of anatomical images. Conclusion: By permitting real-time confirmation of tube position, direct vision may reduce risk of lung complications. The preliminary operator guide requires validation in larger studies.